Analysis of Legal Protection Measures on Children’s Rape Victims through Child Criminal Judicial Mechanism - Mohamad Andi Rochman; Aryani Witasari; Peni Rinda Listyawati (Law Development Journal, 2022)
The purpose of this study is to examine, identify and analyze the concept of the fulfillment of the rights of victims of protection in the judicial process of criminal acts of child molestation progressively. The approach method used in this research is sociological juridical. The specification of this research is descriptive analytical. Article 90 of the Juvenile Justice System Law concerning children who are victims of criminal acts of obscenity have the right to rehabilitation (Recovery to physical and mental and social medical, both inside and outside the Witness and Victim protection institution), Provision of Compensation (Restitution), and Providing compensation. In the process of investigating and prosecuting children's cases, in conducting an investigation of children's cases, investigators are required to ask for considerations or suggestions from community advisors. The process of examining children, apart from the absence of official attributes used in the trial, the difference between adult and child trials is the closed trial system. The examination process at the trial court, the judge in examining the child's case in the children's trial is declared closed to the public except for the reading of the verdict. The concept of the fulfillment of victim protection rights in the judicial process of child obscene crimes can be concluded progressively, namely first, Cross Examinitation. Second, the principle of fast, simple and low cost justice (systematic resocialization of the offender).